Penggunaan Media Kaligrafi dalam Meningkatkan Prestasi Belajar Mata Pelajaran Qur’an Hadits pada Siswa Kelas VII di MTs Darul Abidin NW Gerisak Semanggeleng - Zakaki, Zakaki (TSAQOFAH, 2021)
The background of this research is to see that in general the use of calligraphy media can improve learning achievement in the Qur'an and Hadith subject for Class VII students at MTs. At the data collection stage, there are several designs or research stages used in data collection, including the planning stage, namely planning activities for problem solving. This stage is in the form of drafting an action plan that explains what, why, when, where, by whom, and how the action will be carried out. Stage of Action Implementation (Acting). In this case the teacher acts as an implementer of learning activities as well as an observer. Observation att this stage, the researcher made observations and recorded all the things that were needed and happened during the implementation of the action. Next Reflection (Reflecting) Reflection (Reflecting). With this 4 method, the learning outcomes in Qur'an Hadith lessons with the use of calligraphy media from cycle I to cycle II show an increase in student learning outcomes in Qur'an Hadith lessons